PERSEPSI DAN MINAT MASYARAKAT TERHADAP BUDIDAYA WALET (Collocalia fuciphaga) DI DESA KUOK KECAMATAN KUOK KABUPATEN KAMPAR - Meizar Efendi; Defri Yoza; M. Mardhiansyah (JURNAL ILMU-ILMU KEHUTANAN, 2018)
Cultivation of Collocalia fuciphaga are non-timber forest products that can generate many profits. In the Kuok village there are people who cultivated Collocalia fuciphaga, but the less of information and knowledge of the community about cultivation of Collocalia fuciphaga, caused the Collocalia fuciphaga business has not been yet maximized, so it’s affected to the sale value of Collocalia fuciphaga nest. This research have purpose to knowledge community perception and interest about cultivation of Collocalia fuciphaga in Kuok Vilagge Kuok Sub-district Kampar Regency. The method used in this research is purposive sampling method. Respondents are selected in this research amounted to 43 respondents, 39 respondents were obtained from all Kuok villagers whose residence was within a radius of 50 m, radius 100 m and 150 m from cultivation of Collocalia fuciphaga location, and 4 respondents are entrepreneurs from cultivation of Collocalia fuciphaga. Data analysis in this research is descriptive qualitative by using percentage analysis technique. The result of research showed that, in generally the community perception of Kuok Village Kuok Sub-district has known about cultivation of Collocalia fuciphaga amounted to 63,12%. The community interest of Kuok village Kuok Sub-district to the cultivation of Collocalia fuciphaga is quite big with the percentage amounted to 63,43%, but 30.76% of community do not yet know about how to cultivate Collocalia fuciphaga properly. As many as 35.89% the community of Kuok Village do not yet know, what the things are needed in cultivating Collocalia fuciphaga.